THE CLIMATE CHANGE IMPACT ON CROPS YIELD - Maria NEDEALCOV (Academy of Sciences of Moldova, 2014)
According to the latest evaluation report on the climate change, issued under auspice of the Intergovernmental Panel on Climate Change (IPCC, 2013) „Current climate change already have a signifi cant impact on the natural ecosystems.” In the Republic of Moldova, regardless of the limited area (33300 square kilometers), regional climate change represents one of the major threats to sustainable development and is one of the biggest environmental problems, with negative consequences for the national economy.